Cognitive impairment in people with previous COVID-19 infection: A scoping review. (September 2022) - Bertuccelli, Margherita; Ciringione, Luciana; Rubega, Maria; Bisiacchi, Patrizia; Masiero, Stefano; Del Felice, Alessandra
Abstract: Severe acute respiratory syndrome coronavirus 2 is a worldwide public health issue. Almost 2 years into the pandemic, the persistence of symptoms after the acute phase is a well-recognized phenomenon. We conducted a scoping review to map cognitive domain impairments, their frequency, and associated psycho-affective disorders in people with a previous COVID-19 infection. We searched PubMed/MEDLINE, Scopus, and PsycInfo to identify relevant reports published between December 1, 2019 and February 21, 2022. We followed the PRISMA (Preferred-Reporting-Items-for-Systematic-Reviews-and-Meta-Analyses) extension for scoping review guidelines. Three independent reviewers selected and charted 25 records out of 922. Memory, attention, and executive functions appeared to be the most affected domains. Delayed recall and learning were the most impaired domains of memory. Among the executive functions, abstraction, inhibition, set shifting, and sustained and selective attention were most commonly impaired. Language and visuo-spatial abilities were rarely affected, although this finding might be biased by the scarcity of reports. Neurological and respiratory conditions were often reported in association with cognitive deficits. Results on psycho-affective conditions were inconclusive due to the low frequency of reported data. Admission to an intensive care unit is not related to cognitive deficits. This review highlighted a potential effect of a previous post-COVID-19 infection on a pattern of memory, attention, and executive functions impairments. These findings need to be confirmed on larger cohorts with comprehensive neuropsychological batteries and correlated to neurophysiological and neurobiological substrates.